Pré-sincronização com folículo persistente em protocolos de sincronização da ovulação a base de GnRH em vacas de leite em lactação - Silva, Luiz Augusto Capellari Leite (2017)
The aim of this study was to evaluate the pre-synchronization using progesterone device for persistent dominant follicle induction in TAI protocols using GnRH and prostaglandin in lactating dairy cows. Currently, there are pre-synchronization protocols for the Ovsynch protocol that present high efficiency, but are long and difficult to fix on dairy farms. Thus, it is important to develop shorter pre-synchronization protocols and with the same efficiency of the main GnRH-based protocol and prostaglandin (Double-Ovsynch) for lactating cows. There are efficient ovulation synchronization protocols that use progesterone and estradiol, but due to a possible prohibition of estradiol esters for use in cattle, this study will be an important alternative in the future when by chance it is forbidden the use of estradiol in cows that produce milk, since is an international trend such action. Finally, the published scientific article will have a high impact, as it can be used by any milk farm in the world.